Tiga Pilar Pertahanan Tubuh Terhadap Influenza: Vaksin, Terapi Antivirus, dan Imunomodulator dalam Perspektif Kedokteran Preventif dan Kuratif - Raymond R Tjandrawinata (PT Dexa Medica, 2025)
Influenza is an acute respiratory infection that continues to pose a global health threat due to its high morbidity and mortality burden. In order to overcome this challenge effectively, an integrative approach is required, encompassing three main pillars: annual vaccination adapted to virus mutation dynamics, the use of antiviral agents targeting viral RNA replication, and immune system strengthening through herbal-based immunomodulators and essential micronutrients. This paper emphasizes the importance of synergy between preventive and curative efforts in modern public health strategies.Immunomodulation, which includes a combination of phytocomponents with vitamin C and zinc, has been shown to enhance innate and adaptive immune responses, improve protection to infection, and support recovery processes.An evidence-based approach integrating these three elements is considered the most relevant strategy for addressing influenza virus evolution and strengthening the population's immunological resilience.